Data Structures in the Multicore Age. - SHAVIT, NIR (Communications of the ACM, 2011)
The article discusses the use of multicore processors and parallel architectures to improve data structures. It argues that a major shift is underway, as of March 2011, in the properties of concurrent data structures and their implementing algorithms. This is expected to cause data structures such as stacks, queues, and heaps to become obsolete, replaced by looser constructs involving randomization and distribution. Software engineers are advised to familiarize themselves with the performance benefits and limitations this involves.